At the southern edge of the European Union : the relations between Egypt and the EU before the revolution of 2011 - Pamilo, Satu (2013)
ABSTRACT AT THE SOUTHERN EDGE OF THE EUROPEAN UNION: The relations between Egypt and the EU before the revolution of 2011 Author: Satu Pamilo Political Science Master`s thesis Department of Social Science and Philosophy Faculty of Social Sciences University of Jyväskylä Supervisor: Professor Mika Ojakangas Spring 2013 Number of pages: 64 p., 1 attachment p.